Translation and validation of the Finnish version of index of dental anxiety and fear (IDAF-4C(+)) among dental students - Tolvanen M; Puijola K; Armfield JM; Lahti S (BIOMED CENTRAL LTD, 2022)
Background: Dental fear accounts for 41% of the non-habitual dental attendance such as visiting only when in pain among adult Finns. Dentists should be able to recognize patients in risk for irregular attendance due to dental fear and measure their fear with valid and reliable instrument that capture the multidimensionality of dental fear. The study's aim was to translate the Index of Dental Anxiety and Fear (IDAF-4C+) into Finnish and test its reliability and validity.Methods: The study population consisted of dental students in a Finnish university (n = 202). The IDAF-4C(+) was back-and forward translated by experts as well as a native English translator, blinded to the original version. Reliability was assessed using Cronbach's alpha. Validity of the IDAF-4C(+) was assessed against the Modified Dental Anxiety Scale (MDAS) using Spearman correlation coefficients and through the use of Exploratory factor analysis (EFA) and between genders using Mann-Whitney U tests.Results: The reliability of the IDAF-4C(+) was good, the Cronbach's alpha being 0.88. The IDAF-4C(+) and MDAS and their subscales were correlated, with coefficients varying between 0.34 and 0.85. Correlations were stronger with the emotional and physiological components of the IDAF-4C(+). EFA revealed one factor explaining 51.7% of the common variance (eigenvalue = 4.6). Women tended to have slightly higher mean scores than men (1.49 vs. 1.36, p = 0.247).Conclusions: The translation and localization of the Finnish version of the IDAF-4C(+) can be considered as providing some evidence of the validity and reliability of the scale. It adds to previously used measures as it considers also the behavioral, cognitive and physiological dimension involved in dental fear.